Enhancing crop resilience through elite pre‐breeding lines with key traits for dry direct‐seeded rice - Paul, Pronob J.; Patil, Suyash B.; Vipparla, Abhilash K.; Sagare, Deepti B.; Jain, Abhinav; Balaraju, E.; Venkateswarlu, Challa; Alam, Shamshad; Anandan, A.; Dash, Sushant; Sah, Rameshwar; MS, Anantha; et al. (Wiley, 2025)
Dry direct-seeded rice (Oryza sativa L.; DDSR) is an alternative to transplanted puddled rice (TPR) that enhances water use efficiency and mechanization and reduces labor, greenhouse gas (GHG) emissions, and global warming potential (GWP). To address the limited availability of DDSR-suitable varieties, we initiated a genomic-assisted breeding program to develop such varieties by combining 19 DDSR and biotic stress-related genes/quantitative trait loci (QTLs), that is, anaerobic germination (qAG9.1, qAG9.2), early emergence (qEMM11.1, qEMM3.1), early vegetative vigor (qEVV9.1), root hair density (qRHD1.1), nodal root count (qNR5.1), culm strength (qCS1.1), lodging resistance (qLDG3.1, qLDG4.1), grain yield (qGYDS1.1, qGYDS6.1, qGYDS9.1, qGYDS10.1), gall midge (Gm4, Gm8), blast (Pi9), and brown plant hopper (Bph3, Bph17), using 11 donor parents in MTU 1010 and IR91648-B-89-B genetic backgrounds. From over 150 introgression lines (ILs), 48 carried 7–15 targeted genes/QTLs. Genotyping with the 1k-RiCA SNP array further revealed 2–49 non-targeted genes/QTLs per IL associated with different biotic, abiotic, yield, and quality-related traits. The ILs were evaluated in DDSR and TPR conditions over 2 years, and the introgressed traits were genotypically and phenotypically validated. We observed a positive correlation between the yield performance of developed ILs in both conditions. The top 10 ILs yielded an average of 5756 kg/ha in DDSR and 5665 kg/ha in TPR conditions. Of the four nominated best performing ILs, two ILs are in the advanced stage of the national varietal release program, and many more ILs are in the nomination process for variety release. These ILs are also potential pre-breeding resources for DDSR-suitable varieties in further breeding programs.